Instabilidade e projetos de vida: as incertezas do mundo no caminho dos estudantes do ensino médio - Francisco, Antônio Marcos (Universidade Federal de São Carlos, 2025)
The concept of a life project (purpose) has become a part of the school curriculum and aims to provide opportunities for the holistic development of students. This new educational context of the 21st century is not disconnected from social reality, and the instability of the contemporary era can be an indicator of problems in high school students’ life projects. Bauman (2001) and Beck (2011) present two characteristics of modernity. They can influence these young people in the construction, execution and conquest of their projects: instability and individualization process. Objective: The present research has three objectives: to analyze and discuss the future expectations that high school students and high school graduates have in their life projects (purpose) and investigate if the instability of liquid modernity, historical moment in which they live, can limit your future plans (purpose) to short-term experiences. We realized during the reading of the theoretical framework that the process of individualization is another aspect of liquid modernity that needed to be discussed. Because it tends to influence these young people to consider the execution and results obtained with their life projects as an individualized responsibility. Methodology: The research brings together two data collection instruments: first, a questionnaire with open and closed questions is applied. Students from a school in the state network of Minas Gerais answered the questions at the end of the academic year 2022 and beginning of the academic year 2023; as a second data collection instrument, we conducted some collective conversations with students who left high school. This occurred in June 2023 and at the end of the first quarter of 2024. In these collective conversations, these young people were able to discuss the results obtained or not with their life projects. Results: The purposes are essential for these young people as they can assist them in following path that aligns with their desires, wishes, and intentions. The purpose (life project) can help young people become more aware of the choices that guide their life stories. But according to the research, there are two aspects of liquid modernity that affect the construction and execution of these life projects. The first is the social, cultural and economic instability that makes the visualization of their future uncertain. And the perception of young people is that they are solely responsible for the results that can be obtained with their future plans. Certain contradictions were also observed in the educational proposals. The school that welcomes youth offers in the school curricula spaces for reflection and construction of these purposes, at the same time, presents as a task of education the development of skills so that these young people become able to adapt flexibly to the labor market. Associating predominantly the purposes to the flexibilization produced by the logic of capital. These purposes require longer periods for their realization, if the young person develops the competence of flexibility, consequently, their purposes can be summarized as short-term plans and episodic experiences. Another problem is also present. If these young people assume the role of protagonist in all phases of life projects, such as construction, execution and results, this can influence their perceptions about these projects, because social and economic limitations may be disregarded and, consequently, the whole project of life is visualized as a result of their dedication or personal effort. If you lack dedication, you will experience frustration. Conclusion: The educational task should enable these young people to receive an increasingly critical training that motivates them to fight for the transformation of this unstable and individualized world into something more hospitable for their projects and life trajectories.
Instability and life projects: the uncertainty of the world in the trajectory of high school students
Keywords: Projetos de Vida; Modernidade Líquida; Juventude; Educação; Mercado de Trabalho; Purpose; Liquid Modernity; Youth; Education; Labor Market; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO